Criminal Femmes Fatales in American Hardboiled Crime Fiction - Jaber, Maysaa Husam; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book fills a gap in both literary and feminist scholarship by offering the first major study of femme fatales in hardboiled crime fiction. Maysaa Jaber shows that the criminal literary figures in the genre open up powerful spaces for imagining female agency in direct opposition to the constraining forces of patriarchy and misogyny.
Keywords: Fiction; America-Literatures.; Gender Studies; North American Literature